Effect of Giving Warm Compress Therapy and Bay Leaf Decoction to Scale Level Gout Arthritis Pain - Steffi Eka Nindyastuti Wijaya; Andriyani Mustika Nurwijayanti; Dona Yanuar Agus Santoso (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Gout arthritis is a disease in which joint inflammation that caused by excess uric acid in the joint. The prevalence of joint disease in Indonesia is 7.3% in 2018 and the prevalence of prevalence of joint/ rheumatic/ rheumatic disease 20.1%, the prevalence of Gout Arthritis in Central Java is 25.5%. The major problem in gout artrhitis is pain with mild scale to unrestrained. Efforts to overcome joint pain can be done with pharmacological either non-pharmacological therapy. The non- pharmacological therapies is warm compresses and boiled bay leaves, that believes can reduce pain. The purpose of this study was to determine the effect of warm compresses and bay leaf stew on the level of gout arthritis pain scale. This study used a quasi-experimental design with pretest-posttest with control group. 52 respondents were selected using total sampling technique. This study uses the Mann Whitney test with α 0.05. The results of this study showed p value 0.001 (p <0.05) which means there is a difference between the level of pain scale in patients with gout arthritis before and after warm compress therapy and giving bay decoction. For people with gout arthritis pain, should uses non-pharmacological interventions such as warm compress therapy or take a bay leaf stew to reduce the scale of pain.